Decolonial thinking as an alternative to “reverse racism” in soccer - Nogueira, Otávio; Steffen, João Alberto; Ferreira da Silva, Gilberto (Universidad Pedagógica y Tecnológica de Colombia, 2020)
This article addresses the issue of reverse racism in soccer, considered as another subjugation mechanism of the elite of white people, and the criticism of this prejudice. The main objective is to propose an alternative “other” to fight “reverse racism” in soccer, beyond academic criticism. This is a descriptive and bibliographic study, with reflections based on theoretical contributions of thinkers, mainly Latin American. As an alternative “other”, an intercultural project is proposed for the discipline of soccer in Physical Education, with emphasis on decolonial thinking, both in college and in school. It is understood that, in order to respond to the competency dimensions required for an alternative “other”, the physical education teacher must know the theoretical body that supports his field of knowledge and its connection with other areas, as well as the popular knowledge as part of thinking and doing science. We bet on the physical education professional to break the dichotomy where the place for the physical is outside the classroom and the place for the intellect is inside, and to rethink school sports as a social practice of collective participation.